A single-cell transcriptomic atlas elucidates the hair cycle and apoptosis mechanisms in goat hair follicles - Zhang, Chongyan; Yang, Feng; Liu, Zhihong (Frontiers in Cell and Developmental Biology, 2025)
To explore the molecular mechanism of hair follicle apoptosis in the goat hair cycle, single-cell transcriptome sequencing was performed on 8,214 hair follicle cells in the Anagen period, Catagen period, and Telogen period. We identified nine cell types and found that Matrix cells (MCs) enriched the Wnt signaling pathway and apoptosis-related genes. Further studies revealed the key dynamic genes (such as KRT19, API5) and regulatory factors (such as MSX2, LEF1) that determine the fate of MCs. This study mapped a high-resolution cell map of goat hair follicle apoptosis, providing new insights and diagnostic biomarkers for programmed cell death.